The Changing Face of Orthopaedic Education: Searching for the New Reality After COVID-19 - Kevin D. Plancher, M.D., M.P.H; Jaya Prasad Shanmugam, M.D; Stephanie C. Petterson, M.P.T., Ph.D (Elsevier, 2020)
The COVID-19 pandemic has had immediate impact on the practice of medicine and on orthopaedic education. As the practice of social distancing has been put into place to help slow the spread of disease as well as to conserve medical supplies and equipment, elective surgery has come to a grinding halt. This dramatic change has forced our leaders to evaluate critically the delivery of education and skills training for our residents, fellows and all orthopaedic surgeons. We must continue to develop technologies, such as virtual meeting platforms, distance learning, simulation-based training, virtual reality and augmented reality to open up the new world of orthopaedic education.